THE PROBLEM OF MOTIVATION IN THE LINGUISTIC SIGN - Utanova , Vazirakhon Makhmudjon kizi (Educational Research in Universal Sciences, 2023)
The article describes the expressiveness and expression of linguistic signs, the issue of motivation in them, and the opinions of researchers on this topic.